2004
DOI: 10.1111/j.1095-8339.2004.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Orobanche (Orobanchaceae) from south-eastern Spain

Abstract: A new species, Orobanche portoilicitana A. Pujadas & M. B. Crespo (sect. Trionychon Wallr.) is described from the south-eastern coast of the Iberian Peninsula. This species inhabits coastal sand dunes where it is parasitic on Centaurea species. It is characterized by its dense, many-flowered inflorescences, which bear usually erect, pale bluish flowers with long apiculate anthers. Several morphological features relate the new species to O. olbiensis (Coss.) Nyman, a plant known only from southern France, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…have been described (Foley 1998, 2004, Carlón et al . 2005, 2008, Pujadas-Salvà & Crespo 2004, Pujadas-Salvà 2008), previously neglected species resurrected (Zázvorka 2010, Frajman et al . 2011), and new localities, sometimes far outside the previously known distribution range, (re)discovered (Pusch 2000, Carlón et al .…”
Section: Introductionmentioning
confidence: 99%
“…have been described (Foley 1998, 2004, Carlón et al . 2005, 2008, Pujadas-Salvà & Crespo 2004, Pujadas-Salvà 2008), previously neglected species resurrected (Zázvorka 2010, Frajman et al . 2011), and new localities, sometimes far outside the previously known distribution range, (re)discovered (Pusch 2000, Carlón et al .…”
Section: Introductionmentioning
confidence: 99%
“…Foley (2000) demonstrated that Orobanche rechingeri is conspecific with O. holotype: COA 31083), has a widespread distribution in the Mediterranean. It has also been recorded from Morocco, Algeria, Tunisia, Libya and Egypt (except Sinai, Pujadas & Crespo 2004;Carlón & al. 2005Carlón & al.…”
Section: R El Moknimentioning
confidence: 96%
“…Recent approaches have shown a greater tendency than the earlier conservative treatment of Chater & Webb (1972) to treat host specific races within the genus as distinct species, these often demonstrating both a narrow geographical and host range. This has led to a spate of new species being described in the Mediterranean, Asia Minor and the Middle East in the last two decades (see for example: Pujadas-Salva & Crespo, 2004;Pujadas-Salva et al, 2005, Pujadas-Salva et al, 2008Domina & Danin, 2014;Zare & Dönmez, 2014;Piwowarczyk, 2015). Delineating taxa objectively and reliably is important for informing ecological surveys and for setting conservation priorities: for example in the British Isles, the native subsp.…”
Section: Host Range and Specificitymentioning
confidence: 99%